Synthesis of indolo[3,2-b]carbazole-based new colorimetric receptor for anions: A unique color change for fluoride ions - Mahapatra, Ajit Kumar; Hazra, Giridhari; Sahoo, Prithidipa (Beilstein Journal of Organic Chemistry, 2010)
A novel indolocarbazole-based chemosensor 1 containing hydrogen bond donor moieties has been established as a selective colorimetric and fluorometric sensor for F− in CH3CN/H2O (4:1 v/v). Upon the addition of a series of tetrabutylammonium salts to receptor 1 in aqueous CH3CN, only when the counter ion was F− was a significant color change (from light violet to dark orange) observed.
Keywords: anion binding; colorimetry; fluorescence quenching; fluoride binding; indolocarbazole